Critical Discourse Analysis of Some Selected Iraqi Folk Proverbs - Lecturer. Huda Hadi Badr (Thi Qar Arts Journal, 2021)
This study delves into critical discourse analysis (CDA) of some selected Iraqi folk proverbs(henceforth IFPs). It aims at detecting the ideological themes embedded in IFPs referring to certain proverbial groups of people. The significance of the present study is to find out the different forms of prejudice against these groups of people in the Iraqi Arab culture. The proverbs referring to the proverbial groups of people have been collected from some important compilations and they have been analyzed depending on their interpretation in the compilations in which they occur. Moreover,  for the sake of analysis, these proverbs have been selected on the basis that they have not been handled from CDA perspective. In addition, to discover the underlying  ideologies in the selected proverbs, a qualitative approach has been used. Furthermore, twenty seven proverbs have been selected and only nine samples have been analyzed to uncover the forms of prejudice against the proverbial groups of people whether in the structure or the structure and the function of IFPs. The findings arrived at in this study involve the following forms of prejudice: discrimination against people with special needs, racism against the blacks, sexism, discrimination against certain households members of the same degree of kinship  and tribal intolerance against M‘dān tribe.